Micro-systems mechanics VOLUME III - Lin, Rongming (2008)
Including: 3 parts. With decreasing flying height of the slider arm in hard disk drives, the thin film on the disk surface becomes more and more critical for a stable working condition. In this project, the spreading behaviour of thin liquid PFPE on hard disk surface was investigated theoretically. Due to the thickness of the lubricant film, the impact of slip at the boundary was taken into consideration. A first-order slip model was developed. The diffusion coefficient Ds(h) was modified by incorporating the effective Knudsen number and molecular weight. It is found that slip has to be negative to ensure a maximum value of Ds(h) at a lubricant thickness of 1 nm.